HAK HAK KOLEKTIF DALAM SISTEM HUKUM PERTANAHAN (Suatu Analisis Mengenai Fungsi Hukum Dalam Konflik Pertanahan) - Anang Husni (Masalah-Masalah Hukum, 2011)
The Collective Right (Hak Ulayat, Hak Paer in the community of Sasak tribe in Lombok Island) up to m this time is not configured yet definitely m the National Law System. This matter affects in the community/society welfare depreciation. Law as normative standard in this research is showed and functions to integrate the land matters conflict to increase the standard of community/society life. With reference to that, it is found the holistic approach in solving the conflict.